Rancang Bangun Aplikasi Baca Buku Digital “UMKUPEDIA” Berbasis Website Menggunakan Framework Laravel - Fadilah, Riki Muhamad; Sofhian Fazrin Nasrulloh (Indo-MathEdu Intellectuals Journal, 2025)
Dependence on third-party services causes problems because the management of digital books becomes inflexible and inefficient, which limits students' access to academic reading materials. This research aims to design, implement, and test a digital book reading application "Umkupedia" based on a website using the Laravel framework. The background of this research is the need for a digital book repository at Muhammadiyah University of Kuningan. This research uses the Research and Development (R&D) method with a waterfall model that includes five stages: analysis, design, development, testing, and maintenance. The research population involves all academic civitas of Muhammadiyah University of Kuningan. This application aims to improve accessibility, flexibility, and serve as a substitute for third-party services. The results of the functionality testing indicate that all 20 features tested operated successfully as designed without any errors or discrepancies in workflow. The library expert test using a professional principle approach and Likert scale showed a feasibility percentage of 92% (category 'very feasible'). Usability testing by 10 academic staff yielded a result of 85.17% (category 'very feasible'). Therefore, it can be concluded that the digital book reading application 'Umkupedia,' based on a website using Laravel, meets the aspects of functionality and usability and is suitable for implementation in the operations of a college library.